2004
DOI: 10.3390/e6020257
|View full text |Cite|
|
Sign up to set email alerts
|

Statistical Convergent Topological Sequence Entropy Maps of the Circle

Abstract: A continuous map f of the interval is chaotic iff there is an increasing of nonnegative integers T such that the topological sequence entropy of f relative to T, hT(f), is positive [4]. On the other hand, for any increasing sequence of nonnegative integers T there is a chaotic map f of the interval such that hT(f)=0 [7]. We prove that the same results hold for maps of the circle. We also prove some preliminary results concerning statistical convergent topological sequence entropy for maps of general compact me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The editors were made aware that a paper published in Entropy in 2004 [1] may have plagiarized an earlier paper by Roman Hric published in 2000 [2]. After checking with specialized plagiarism software, we found that this claim is indeed correct and almost the entire paper is a verbatim copy of the earlier one.…”
mentioning
confidence: 85%
“…The editors were made aware that a paper published in Entropy in 2004 [1] may have plagiarized an earlier paper by Roman Hric published in 2000 [2]. After checking with specialized plagiarism software, we found that this claim is indeed correct and almost the entire paper is a verbatim copy of the earlier one.…”
mentioning
confidence: 85%